Effects of customer relationship management, customer perceived value and customer socio - demographic characteristics on bank customers’ loyalty in Ghana - Agbemabiese, George Cudjoe (2018)
Customer relationship management (CRM) has emerged as one of the most preferred modern strategies for enhancing superior customer value and improving customer loyalty in the banking sector globally, considering the intense competit ive landscape. Empirical evidence has however revealed that about 50% of CRM implementations have failed to achieve their expected outcomes, leading to some scholars questioning the direct and unconditional effect of CRM on customer loyalty. Despite some efforts to study the generational mechanism by which CRM influences customer loyalty, very little efforts have been made to examine the mediating role of customer perceived value in the relationship between CRM and customer loyalty in the banking industry. This study was conducted to bridge this literature gap by developing an integrated model which explains the relationships between CRM, customer perceived value and customer loyalty within the Ghanaian banking industry. Using a quantitative methodology, a self-administered questionnaire was used to collect data from 809 customers of retail banks in Ghana and analysed using Structural Equation Modelling of Partial Least Squares (PLS-SEM). The findings show that all dimensions of CRM except customer knowledge management positively and significantly influenced customer loyalty. Additionally, a positive relationship existed between CRM and customer perceived value. Customer perceived value partially mediated the relationship between CRM and customer loyalty with account type and gender moderating the relationships between CRM and customer perceived value and between customer perceived value and customer loyalty respectively. The study contributes significantly to the body of knowledge by demonstrating how the Resource Based View and Equity theories could be integrated to improve customer value and customer loyalty in the banking industry. The study also challenges banks to deploy their CRM resources equitably in their efforts to improve customer loyalty in the banking sector.